Expression of Basic Emotions in Pictures by German and Vietnamese Art Therapy Students – A Comparative, Explorative Study - Danner-Weinberger, Alexandra; Puchner, Katharina; Keckeis, Margrit; Brielmann, Julia; Tri, Minh Thuy Thi; Le Hoang, The Huy; Nguyen, Luan Huynh; Köppelmann, Nikolai; Rottler, Edit; Gündel, Harald; von Wietersheim, Jörn (Frontiers in Psychology, 2019)
During art therapy self-experience workshops in Vietnam and Germany, the authors noticed that there were differences in how the groups expressed their feelings in paintings. This led the authors to a comparative, explorative study. In this study, each of the 29 workshop participants from Germany and Vietnam were instructed to draw pictures related to basic emotions like sadness, disgust, anger, or happiness. Then, the paintings were evaluated by using rating scales with which formal and content-oriented criteria can be assessed. The interrater reliability was good. The results showed some statistically significant differences. The Vietnamese participants used smaller formats and more colors with stronger color application. They preferred simpler forms than the Germans. The German participants painted in a more abstract manner, while the Vietnamese participants used more concrete and tended to scenic expressions (representation of stories). There are some reasons which might explain these differences: It is known that cultural influences play an important role in the arts as well as in the way creative arts are taught in a particular society. The expression of emotions is culture-specific as well. The Vietnamese participants were, however, interested in the possibilities art therapy offers and felt that there are good chances for this therapy to develop in their country.